2020
DOI: 10.4103/tcmj.tcmj_113_19
|View full text |Cite
|
Sign up to set email alerts
|

Significant association factors of bone mineral density in Taiwan adults

Abstract: Objective: To examine the biofactors associated with bone mineral density (BMD) in southern Taiwanese adults. Materials and Methods: The medical records of 3242 adults who underwent health examinations between June 2014 and February 2018 at a regional hospital in southern Taiwan were reviewed. The data collected included health history, anthropomorphic characteristics, clinical laboratory results, biochemical parameters, and BMD. The data were used to identify the biofa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…[11,12] Recently, its serum levels were correlated with bone metabolism and BMD. [13][14][15][16][17] Our study investigated this correlation in adults aged 20 to 59 years and found a negative correlation between serum ALP levels and pelvic BMD, which persisted after adjusting for confounders (Table 2). Females exhibited a more significant negative correlation between serum ALP levels and pelvic BMD than that exhibited by males.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…[11,12] Recently, its serum levels were correlated with bone metabolism and BMD. [13][14][15][16][17] Our study investigated this correlation in adults aged 20 to 59 years and found a negative correlation between serum ALP levels and pelvic BMD, which persisted after adjusting for confounders (Table 2). Females exhibited a more significant negative correlation between serum ALP levels and pelvic BMD than that exhibited by males.…”
Section: Discussionmentioning
confidence: 83%
“…[11,12] Recently, its serum levels were correlated with bone metabolism and BMD. [13–17] Our study investigated this correlation in adults aged 20 to 59 years and found a negative correlation between serum ALP levels and pelvic BMD, which persisted after adjusting for confounders (Table 2).…”
Section: Discussionmentioning
confidence: 85%